Corporate Governance and Accounting Conservatism: The Moderating Role of Family Ownership - Mohammed, Nishtiman; Ismail, Ku Nor Izah Ku; Amran, Noor Afza (International Business and Accounting Research Journal, 2019)
This study objective is to investigate the influence of board characteristics and audit committee characteristics on accounting conservatism with respect to the influence of family ownership in Turkey. The findings explained that clients’ demand for accounting conservatism improved because of board characteristics (e.g. board size, independence & women on board) and the audit committee characteristics (e.g. audit committee independence and audit committee expertise). Hence, the family ownership undermines the impact of board characteristics and the audit committee characteristics to demand accounting conservatism, which will be unfavorable outcome for the minority shareholders. Thus, this study suggests that regulators should increase law enforcement to improve corporate governance in Turkey to accommodate the unique characteristics of family ownership and offer a protected environment for minority shareholders.